2019
DOI: 10.1039/c9ra04842a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient crystallization of AlPO4-5 accelerated by a rotating hydrothermal synthesis route

Abstract: Compared with static hydrothermal synthesis, the crystallization rate of an AlPO 4 -5 molecular sieve has been accelerated distinctly by a rotating hydrothermal synthesis route with obviously decreased crystal particle size, which is assumed to be ascribed to the increased nucleation centers, accelerated crystal nucleation and growth processes; five-coordinated Al is dominant in the initial reaction gel, and the assembly from amorphous Al species to long-range ordered crystals is mainly contributed by the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…13 It is found that the relative crystallinity of the RS-series catalysts increases slightly with the increase of the rotation rate during the initial 0.5 day, which is ascribed to the accelerated crystal nucleation and consequently crystal growth of zeolite under a relatively high rotation rate. 20,21 The UV-vis spectra shown in Fig. S1 † indicate that four-coordination framework titanium is the fundamental Ti species in RS-series catalysts.…”
Section: Characterization and Catalytic Application Of Cczl Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 It is found that the relative crystallinity of the RS-series catalysts increases slightly with the increase of the rotation rate during the initial 0.5 day, which is ascribed to the accelerated crystal nucleation and consequently crystal growth of zeolite under a relatively high rotation rate. 20,21 The UV-vis spectra shown in Fig. S1 † indicate that four-coordination framework titanium is the fundamental Ti species in RS-series catalysts.…”
Section: Characterization and Catalytic Application Of Cczl Materialsmentioning
confidence: 99%
“…It is well-known that the hydrothermal method is an extensively used method to prepare zeolite and related materials, which can be conducted under static or rotating conditions, 20,21 and the electrostatic and van der Waals interactions play a crucial role in the formation of nuclei with preferred geometries. 22 Herein, a new switch crystallization strategy (SCS) is developed to synthesize MWW zeolite lamellas by the combination of crystallizations under rotating and static hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%